A Role for Timely Nuclear Translocation of Clock Repressor Proteins in Setting Circadian Clock Speed - Lee, Euna (The Korean Society for Brain and Neural Science, 2014)
By means of a circadian clock system, all the living organisms on earth including human beings can anticipate the environmental rhythmic changes such as light/dark and warm/cold periods in a daily as well as in a yearly manner. Anticipating such environmental changes provide organisms with survival benefits via manifesting behavior and physiology at an advantageous time of the day and year. Cell-autonomous circadian oscillators, governed by transcriptional feedback loop composed of positive and negative elements, are organized into a hierarchical system throughout the organisms and generate an oscillatory expression of a clock gene by itself as well as clock controlled genes (ccgs) with a 24 hr periodicity. In the feedback loop, hetero-dimeric transcription factor complex induces the expression of negative regulatory proteins, which in turn represses the activity of transcription factors to inhibit their own transcription. Thus, for robust oscillatory rhythms of the expression of clock genes as well as ccgs, the precise control of subcellular localization and/or timely translocation of core clock protein are crucial. Here, we discuss how sub-cellular localization and nuclear translocation are controlled in a time-specific manner focusing on the negative regulatory clock proteins.